Understanding the Digital Platform Economy: Effect of Airbnb on Housing in Indian Cities - Sridhar, Kala Seetharam (Housing policy debate, 2022)
This article answers the question: What is the effect of Airbnb on rents and housing prices? Based on theory and empirical evidence, we expect that in cities where Airbnb is active, rental accommodation and housing would be relatively more expensive. This is because we assume that such units were withdrawn from the housing market and excess capacity of houses can be used. We distinguish between the rents of one- , two- , and three-bedroom apartments, in addition to housing prices in major Indian cities. Accounting for the endogeneity of Airbnb density, we find that the Airbnb density has a significant effect in terms of raising rents of apartments of different sizes as well as increasing housing prices. The magnitude of our estimates implies an increase of up to 0.08% in the rent of two-bedroom apartments, 0.14% in the rents of three-bedroom apartments, and 0.39% in housing prices per square foot, for every 1-percentage-point increase in Airbnb density. These effects are higher than those found in some existing studies, but lower than those found by others. The policy implications of the research and caveats of the data and research are summarized.